Prevalensi Kejadian Pediculosis Capitis Pada Anak Panti Asuhan di Kota Palangka Raya - Lifrie Merrary; Indria Augustina; Astrid Teresa; Arif Rahman Jabal; Dian Mutiasari (Direktorat Politeknik Kesehatan Makassar, 2024)
Background: Pediculosis capitis in Indonesia is often also called mites. Pediculosis capitis usually attacks the child population in the age group of 6-12 years. Pediculosis capitis easily attacks children, this is because children still do not understand and pay attention to hygiene. Factors that increase the risk of developing pediculosis capitis are gender, frequency of washing hair, sharing combs and hair accessories, sharing beds, long hair, and hair type. Objective: This study aims to determine the prevalence of pediculosis capitis in orphanage children in Palangka Raya City. Method: This type of research uses a descriptive method with a cross sectional design. Cross sectional research is a type of research that measures data at one time and the research subjects are observed only once at a time. Results: In this study, the prevalence of pediculosis capitis infestation was found in 36 girls (47.3%) and 4 boys (5.2%). Conclusion: Research conducted on children in four orphanages in Palangka Raya City found that the prevalence of pediculosis capitis was 50% of the 76 population. Keywords: Pediculosis Capitis, Prevalence